Model Variasi Mengajar dan Pembelajaran Guru PAI di SMP Muhammadiyah 6 Kota Yogyakarta - Albany, Sulistiono Shalladdin; Rochman, Fauzi (Universitas Pendidikan Indonesia Kampus Serang, 2022)
In the phenomenon of the learning process that occurs in the classroom, not infrequently students are given the assumption of being an empty container that is mandatory and can be filled with various teaching materials whatever the teacher wants. There are few teachers who are sensitive and considerate to the feelings or emotions of students even to their readiness in learning, this is contrary to the expectations of the quality of education that occurs. The existence of variations in teaching and learning makes expectations of the quality of education perfect to aspire to. This study intended to explore more deeply the variations in teaching and learning of Islamic Religious Education teachers in order to achieve maximum core competencies at Junior High School of Muhammadiyah 6 Yogyakarta. In this research, the subject is the Islamic Religion teacher, and the information was obtained from other subject teachers. The data was collected by the method of observation, and interviews. Data reduction, data presentation, and conclusion drawing become the validity of the data collected. The results of this study indicate that there are 2 variations of teaching and learning in the context of achieving spiritual and social core competencies with the lecture method containing advice and awareness of life. For core competencies, knowledge and skills are carried out with variations in project methods, video analysis, practice, and variations in learning during a pandemic with online learning.